Friction equation for uniform flow in channels of large relative roughness - Lillie, Edwin (Department of Civil Engineering, 2016)
This thesis is an experimental investigation of the roughness problem in open channel flow. A literature review is given on the previous research done on friction factors. It is done in chronological order, so that the historical development of the friction equation can be seen.